Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739480.2754708
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective Optimization with Dynamic Constraints and Objectives

Abstract: Dynamic Multi-objective Optimization (DMO) is a challenging research topic since the objective functions, constraints, and problem parameters may change over time. Several evolutionary algorithms have been proposed to deal with DMO problems. Nevertheless, they were restricted to unconstrained or domain constrained problems. In this work, we focus on the dynamicty of problem constraints along with time-varying objective functions. As this is a very recent research area, we have observed a lack of benchmarks tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Consequently, the objective functions and constraints on these time-varying parameters make the optimal cooperative relay selection a challenging problem. The research work reported in [118] can be helpful for researchers while designing optimal cooperative relay selection solutions.…”
Section: Open Research Challengesmentioning
confidence: 99%
“…Consequently, the objective functions and constraints on these time-varying parameters make the optimal cooperative relay selection a challenging problem. The research work reported in [118] can be helpful for researchers while designing optimal cooperative relay selection solutions.…”
Section: Open Research Challengesmentioning
confidence: 99%
“…Finally, for performance indicator‐based multicriteria evolutionary algorithms, surrogates have been trained to approximate the hypervolume contribution of a newly created individual in a steady‐state multicriteria evolutionary algorithm using an artificial neural network (Azzouz, Bechikh, & Ben Said, ).…”
Section: State‐of‐the‐art In Surrogate‐assisted Multicriteria Optimizmentioning
confidence: 99%
“…The EI criteria can be used in the selection of evolutionary algorithms (Giannakoglou, ; Emmerich, Beume, & Naujoks, , ; Azzouz, Bechikh & Ben Said, ) or as infill criterion in EGO (Knowles, ; Ponweiser, Wagner, Biermann, & Vincze, ; Shimoyama, Sato, Jeong, & Obayashi, ; Zaefferer et al, ). Efficient exact computation algorithms for the multivariate EI are discussed in the works of Couckuyt, Deschrijver, and Dhaene (); Hupkens, Deutz, Yang and Emmerich ().…”
Section: State‐of‐the‐art In Surrogate‐assisted Multicriteria Optimizmentioning
confidence: 99%
“…Nevertheless, both procedures are sensitive to the choice of the population ratio ζ and the change frequency. A new version of this algorithm was proposed in Azzouz et al (2015) to deal with dynamic constraints by replacing the used constraint-handling mechanism by a more elaborated and self-adaptive penalty function. Moreover, authors proposed a set of test problems that extended a suite of static constrained multi-objective problems.…”
Section: Diversity-based Approachesmentioning
confidence: 99%